2020
DOI: 10.1039/d0cp04132g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-dependent termination, size and stability in polyynes synthesized via laser ablation in liquids

Abstract: In recent years there has been a growing interest in sp-carbon chains as possible novel nanostructures. An example of sp-carbon chains are the so-called polyynes, characterized by the alternation of...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(75 citation statements)
references
References 54 publications
3
72
0
Order By: Relevance
“…Spectroscopic analyses confirm that the achieved LCCs are hydrogen capped sp hybridized carbon structures with alternating single and triple bonds [ 24 , 25 ], while Au NPs are spherical with an average size of 5 nm [ 25 , 26 ]. However, the poor colloidal stability of the obtained LCCs leads to reorganization phenomena via crosslinking reaction in sp structures [ 27 ]. To overcome this limit, the employment of spacers at the end of an sp-carbon chain, such as the embedding of these carbon chains in solid matrices (PVA, SiO , metal nanoparticles), is an efficient strategy that helps to avoid sample degradation [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic analyses confirm that the achieved LCCs are hydrogen capped sp hybridized carbon structures with alternating single and triple bonds [ 24 , 25 ], while Au NPs are spherical with an average size of 5 nm [ 25 , 26 ]. However, the poor colloidal stability of the obtained LCCs leads to reorganization phenomena via crosslinking reaction in sp structures [ 27 ]. To overcome this limit, the employment of spacers at the end of an sp-carbon chain, such as the embedding of these carbon chains in solid matrices (PVA, SiO , metal nanoparticles), is an efficient strategy that helps to avoid sample degradation [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the presence of a liquid layer strongly confines the plasma plume compared to ablation experiments performed in vacuum or low-pressure gas atmosphere, reducing the area of target ablation to approximately the laser spot and increasing the temperature and pressure inside the plasma [21,34,39,40]. At the plasma-liquid interface, the high temperatures cause the degradation, ionization, and pyrolisis of the solvent molecules [34,[41][42][43]. During this process, highly reactive species (e.g.…”
Section: Fundamental Process Occuring During Plalmentioning
confidence: 99%
“…This elongation process, called polymerization, competes with the hydrogenation process that instead tends to terminate the chain with a hydrogen atom [60]. Moreover, in the case of a carbon-based target or powder, both the target and the solvent provide carbon atoms or radicals for the polymerization mechanism [42]. Indeed, the high temperatures reached by the plasma plume cause the atomization of the several atomic layers of the target surface and induces the degradation of the solvent promoting the release of carbon atoms and/or C n radicals [42,60,62,63].…”
Section: Mechanisms Of Formation Of Polyynes By Plalmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Casari et al recently reported the detection of hydrogenterminated oligoynes as long as H-(CRC) 11 -H via pulsed laser ablation of a graphite target in acetonitrile or alcohol solvents. 50 For the controlled laboratory synthesis of longer oligoynes attention turned to attaching very bulky aryl end-groups to prevent intermolecular reactions. Hirsch et al characterised a (CRC) 10 oligoyne with dendron-substituted aryl end-groups.…”
Section: Highlights Of Oligoyne Synthesismentioning
confidence: 99%